2013
DOI: 10.1088/1748-9326/8/2/024034
|View full text |Cite
|
Sign up to set email alerts
|

Satellite-based primary forest degradation assessment in the Democratic Republic of the Congo, 2000–2010

Abstract: Primary forest extent, loss and degradation within the Democratic Republic of the Congo (DRC) were quantified from 2000 to 2010 by combining directly mapped forest cover extent and loss data (CARPE) with indirectly mapped forest degradation data (intact forest landscapes, IFL). Landsat data were used to derive both map inputs, and data from the GLAS (Geoscience Laser Altimetry System) sensor were employed to validate the discrimination of primary intact and primary degraded forests. In the year 2000, primary h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
46
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(49 citation statements)
references
References 34 publications
2
46
0
1
Order By: Relevance
“…With global coverage, the regularly acquired largest historical archive and freely available space-based earth observations, Landsat imagery is preferred for monitoring tropical forests (Vieira et al 2003;Salovaara et al 2005;Kumar et al 2010;Potapov et al 2012;Das and Singh 2013;Zhuravleva et al 2013). Several studies have reported deforestation and forest area changes in Indonesia using Landsat satellite data (Curran et al 2004;Hansen et al 2009, Miettinen andLiew 2010;Margono et al 2012).…”
Section: Other Actors' Role In Forest Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…With global coverage, the regularly acquired largest historical archive and freely available space-based earth observations, Landsat imagery is preferred for monitoring tropical forests (Vieira et al 2003;Salovaara et al 2005;Kumar et al 2010;Potapov et al 2012;Das and Singh 2013;Zhuravleva et al 2013). Several studies have reported deforestation and forest area changes in Indonesia using Landsat satellite data (Curran et al 2004;Hansen et al 2009, Miettinen andLiew 2010;Margono et al 2012).…”
Section: Other Actors' Role In Forest Managementmentioning
confidence: 99%
“…Brazil and Indonesia together accounted for 52% of the world's net loss of forest during this same period. Especially, decrease of primary forests is particular concern, accounting for 38% of the 15.79 million ha of forest cover loss for Indonesia for the period 2000-2012 (Hansen et al 2013). This forest loss has contributed significantly to greenhouse gas (GHG) emissions, with emissions from deforestation and decay of biomass accounting for approximately 17.4% (CO 2 equivalent) of the world's GHG emissions in 2004 (IPCC 2007a).…”
Section: Introductionmentioning
confidence: 99%
“…An intact forest landscape (IFL) is an unbroken expanse of natural ecosystem which contains forest and non-forest ecosystems within a current forest zone, showing no signs of significant human activity [4]. This IFL definition was proposed by Greenpeace in 2001 as an approach to provide timely mapping and monitoring of variations in forest extent [5].…”
Section: Introductionmentioning
confidence: 99%
“…While [15] describes the suitability of Earth observation technology to determine conflict trends and improve human security in Africa, [16] discusses land use and land cover (LULC) changes related to conflict by analyzing satellite data as well as social surveys and secondary data. A direct link between detected land cover changes and forest degradation derived from Landsat TM and ETM+ data is drawn by [17][18][19] by explaining the impact of the dramatic armed conflicts in DRC on forest resources.…”
Section: Introductionmentioning
confidence: 99%